Simplifying
9x + 7 = 5x + -3
Reorder the terms:
7 + 9x = 5x + -3
Reorder the terms:
7 + 9x = -3 + 5x
Solving
7 + 9x = -3 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
7 + 9x + -5x = -3 + 5x + -5x
Combine like terms: 9x + -5x = 4x
7 + 4x = -3 + 5x + -5x
Combine like terms: 5x + -5x = 0
7 + 4x = -3 + 0
7 + 4x = -3
Add '-7' to each side of the equation.
7 + -7 + 4x = -3 + -7
Combine like terms: 7 + -7 = 0
0 + 4x = -3 + -7
4x = -3 + -7
Combine like terms: -3 + -7 = -10
4x = -10
Divide each side by '4'.
x = -2.5
Simplifying
x = -2.5